Development of a dryland corn productivity index for Kansas - Bush, Erin Leigh (Kansas State University, 2019)
For many decades, researchers have created indices to rate soil on its ability to produce vegetative growth. The Soil Rating for Plant Growth (SRPG) model was developed by USDA-Natural Resources Conservation Service (NRCS) in 1992 to array soil mapping units relative to their potential to produce dryland commodity crops independent of management. A few years later, the Kansas Department of Revenue (KDR) Property Valuation Division (PVD) began using the SRPG model for land valuation. Since then, the SRPG was updated to a Kansas-specific model, KS-SRPG, later renamed and modified to PRGM-General Crop Production Index (GCPI), and stored in the National Soil Information System (NASIS). In 2003, modifications were made to the GCPI model to develop an irrigated index for Kansas and was termed the Kansas Irrigated Productivity Index (KIPI). KS-SRPG and KIPI are still used by the PVD, but are no longer updated, are not available to the public, and are difficult to understand. Therefore, it is necessary to construct a new model to predict dryland corn productivity for Kansas soil mapping units. This thesis calibrated and validated a new dryland corn index, which is termed the Kansas Commodity Crop Productivity Index (KCCPI) corn submodel. The KCCPI model was built in NASIS with the goal of being available to the public on Web Soil Survey. Corn yield data in NASIS were used to calibrate the model during development. Dryland corn yield data were obtained from Risk Management Agency (RMA) by Common Land Unit (CLU) and regressed against KCCPI for validation. Results during calibration were promising, but KCCPI was not as successful during validation. This suggests that more work needs to be done to the model with more sets of yield data.
Keywords: Productivity; Index; Kansas; Corn; Rating; Crop